Fluorescence Quenching of a Benzimidazolium–based Probe for Selective Detection of Picric Acid in Aqueous Medium. Issue 8 (17th June 2016) - Joshi, Sunita; Kumari, Santosh; Chamorro, Eduardo; Pant, Debi D.; Sakhuja, Rajeev
Abstract: A fluorescent coumaryl linked benzimidazolium salt has been synthesized, characterized and found to be highly selective for nanomolar detection of commonly used explosive picric acid, over other aromatic explosives in aqueous medium. The quenching constant and detection limit of the sensor for picric acid was found to be KSV =1.58 × 10 4 M −1 and 208 nM respectively. The high sensitivity of the sensor toward picric acid can be predominantly attributed to the ground‐state charge‐transfer complex formation based on UV‐visible studies, time resolved fluorescence results and Density Functional Theory (DFT) calculations. Abstract : A novel fluorescent coumaryl linked benzimidazolium salt has found to be highly selective for nanomolar detection of explosive picric acid, over other aromatic explosives in aqueous medium. The quenching constant and detection limit of the sensor was found to be KSV =1.58 × 10 4 M −1 and 208 nM respectively for picric acid. UV‐Visible studies, time resolved fluorescence results and Density Functional Theory (DFT) calculations inferred the ground‐state charge‐transfer complex formation as the predominant quenching mechanism for picric acid detection.